TINJAUAN HUKUM ISLAM TERHADAP PERBEDAAN HARGA TIKET WISATA PADA HARI LIBUR DAN HARI BIASA - Rumanah, Neno; Jamaluddin; Zaini, Ahmad (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2022)
The development of an increasingly advanced era has resulted in many rapid changes, especially the number of tourist attractions that have been built and attracted by many people, so that they are used by people as a promising business opportunity. With varying ticket prices, it is usually determined by the difference in days, such as on weekdays the cost of entering tourist attractions is relatively cheaper than the price of admission on holidays or red dates. The existence of price differences can cause injustice to consumers because the facilities provided by tourist attractions are the same both on holidays and weekdays. Based on the above background, the formulation of the problem in this study are: 1) How to determine the sale and purchase price of entrance tickets at tourist attractions on holidays and weekdays at Aqualand Serang? 2) How do visitors respond to the difference in rates at Aqualand Serang? 3) How is Islamic law reviewing the difference in the price of buying and selling entrance tickets at entertainment attractions on holidays and weekdays at Aqualand Serang?. The purposes of this study are: 1) To find out how to determine the price of buying and selling entrance tickets at entertainment tourist attractions on holidays and weekdays at Aqualand Serang 2) To find out the response of visitors to the difference in rates at Aqualand Serang 3) To find out the review of Islamic law on price differences. buying and selling entrance tickets at entertainment attractions on holidays and weekdays at Aqualand Serang. This study uses qualitative research, research data obtained using observation, interviews and documentation. The conclusion of this study is that Aqualand Serang sets prices according to the needs of tourist attractions and visitor satisfaction. The price difference is also used as a marketing strategy, although there are still some visitors who object to the difference in ticket prices on holidays and weekdays, but in the perspective of Islamic law the difference in the price of buying and selling tourist tickets on holidays and weekdays at Aqualand Serang fulfill the pillars and conditions in the sale and purchase